Zinc Supplementation Enhances Glutathione-Mediated Antioxidant Defense and Glyoxalase Systems to Conferring Salt Tolerance in Soybean (Glycine max L.) - Hassan S. Al-Zahrani; Kamrun Nahar; Hesham F. Alharby; Hameed Alsamadany; Khalid Rehman Hakeem; Mirza Hasanuzzaman (Agronomy, 2022)
In this study, the role of zinc (Zn) in salt-affected soybean (Glycine max L.) was scrutinized by exposing plants to salt stress (150 mM NaCl) alone and in combination with exogenous Zn (priming and/or foliar spray with 1 mM ZnSO4.7H2O). Salt stress decreased plant growth and caused the destruction of chlorophyll and carotenoids. It also disrupted physiological processes and antioxidant defenses, resulting in an oxidative burst. The levels of the toxic metabolite methylglyoxal (MG) rose substantially under salinity. Salinity resulted in a high accumulation of Na+ and decreased K+ which decreased the K+/Na+ ratio. Zn supplementation decreased ion toxicity and improved ion homeostasis in soybean plants. Zn increased glutathione (GSH) levels, decreased glutathione disulfide levels, and increased their ratio in salt-treated soybean plants compared to salt-treated plants without Zn addition. Zn supplementation also upregulated the activities of the glutathione-dependent enzymes glutathione reductase, dehydroascorbate reductase, glutathione peroxidase, and glutathione S-transferase in salt-stressed plants. The enhanced GSH pool and increased activity of GSH-dependent enzymes decreased oxidative damage, as indicated by the reduced levels of H2O2 and malondialdehyde and lower electrolyte leakage. The increased GSH level and high activity of glyoxalase I and glyoxalase II conferred by Zn under salt stress helped to scavenge methylglyoxal. The restoration of photosynthetic pigment levels and increased proline accumulation, together with the recovery of leaf relative water content, were further signs of salt stress recovery and tolerance conferred by Zn supplementation. Our results showed that the antioxidant defense, glyoxalase system and some other physiological parameters were improved by Zn supplementation which contributed to mitigating the effects of salt stress in soybean.